2011
DOI: 10.3109/01443615.2010.536858
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric hysterectomy: A review of cases over 16 years

Abstract: Emergency peripartum hysterectomy (EPH), is performed when life-threatening obstetric conditions occur. The authors attempt to assess the incidence of EPH as well as to investigate risk factors and patients' characteristics. A retrospective study of all cases of EPH performed at the 2nd Department of Obstetrics and Gynecology, Medical School of Athens University, from 1994 to 2009 has been conducted. Data were abstracted from individual medical charts and laboratory records. Among 16,182 deliveries, 15 EPH wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 21 publications
9
63
0
2
Order By: Relevance
“…Historically, the most prevalent indication for emergency PH was uterine atony. However, a number of studies have suggested that abnormal placentation (including placenta previa, increta, accrete, and percreta) is a major risk factor of CSs, which are increasing in number (2,6,8,10,13) and resulting in the higher incidence of emergency PH (1)(2)(3)(4)(5)(6)16). In modern obstetrics, the overall incidence of emergency PH is 0.05%; however, perceptible differences exist in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, the most prevalent indication for emergency PH was uterine atony. However, a number of studies have suggested that abnormal placentation (including placenta previa, increta, accrete, and percreta) is a major risk factor of CSs, which are increasing in number (2,6,8,10,13) and resulting in the higher incidence of emergency PH (1)(2)(3)(4)(5)(6)16). In modern obstetrics, the overall incidence of emergency PH is 0.05%; however, perceptible differences exist in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Peripartum hysterectomy (PH) is a major surgical procedure, typically performed as an emergency measure during or within 24 hours of abdominal or vaginal deliveries due to lifethreatening hemorrhage (1). It has an incidence of0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] It is however lower than those reported from developed countries. [15] This may be because of the higher parity, cultural and religious beliefs, aversion to repeat caesarean section, large numbers of unbooked emergencies and antenatal defaulters in our environment. Also, our institution is an important referral center in this region and most of our cases were referred from outside in moribund condition after complications occurred.…”
Section: IIImentioning
confidence: 99%
“…Such haemorrhage is most commonly due to abnormal placentation45 to 73.3% and uterine atony, accounting for 26.6% to 35.6% percent of peripartum hysterectomies. [1][2][3] Other potential causes of severe intrapartum or postpartum uterine haemorrhage include uterine rupture, leiomyomas, and laceration of uterine vessels. Planned peripartum hysterectomy may be performed in patients with an antepartum diagnosis of placenta accreta or stage IA2 and IB1 cervical carcinoma.…”
Section: Introductionmentioning
confidence: 99%